Deep learning : a practitioner's approach - Patterson, Josh; Gibson, Adam (O'Reilly Media, Inc., 2017)
How can machine learning--especially deep neural networks--make a real difference in your organization? This hands-on guide not only provides practical information, but helps you get started building efficient deep learning networks. The authors provide the fundamentals of deep learning--tuning, parallelization, vectorization, and building pipelines--that are valid for any library before introducing the open source Deeplearning4j (DL4J) library for developing production-class workflows. Through real-world examples, you'll learn methods and strategies for training deep network architectures and running deep learning workflows on Spark and Hadoop with DL4J.- Resumé vydavatel
Includes index.
Keywords: strojové učení; neuronové sítě (počítačová věda); machine learning; neural networks; příručky; elektronické knihy; handbooks and manuals; electronic books